Morbidity and mortality in premature or low birth weight patients with congenital heart disease in three European pediatric heart centers between 2016 and 2020 - De Silvestro, Alexandra; Reich, Bettina; Bless, Sarah; Sieker, Julika; Hollander, Willemijn; de Bijl-Marcus, Karen; Hagmann, Cornelia; Nijman, Joppe; Knirsch, Walter; , the European Association Brain in Congenital Heart Disease; Bekker, Mirielle N.; Benders, Manon J. N. L.; et al. (Frontiers in Pediatrics, 2024)
Background Treatment of preterm and low birthweight (LBW) neonates born with congenital heart disease (CHD) requiring early cardiac intervention remains challenging. We aimed to analyze morbidity and mortality in this combined high-risk patient group. Methods Retrospective cohort study of preterm (<37 weeks gestational age (GA)) and/or LBW neonates (<2500g) born with a diagnosis of CHD which requires invasive cardiac intervention (surgery or catheter) within their first year of life. Patients born from 2016 to 2020, treated in three European pediatric heart centers were included. Results A total of 308 neonates (51% male) with CHD were included. Of those, 237 (77%) were born preterm, 259 (84%) LBW, and 188 (61%) were both. Median (IQR) GA was 35.4 (33.3-36.9) weeks and a mean (SD) birth weight was 2016 (580) grams. CHD was categorized as simple (12%), moderate (64%), or severe (24%). Overall complication rate was 45% and highest in patients with severe CHD (p=0.002). One-year mortality (19%) was associated with severe CHD type, low relative birth weight in patients with genetic diagnoses, and low GA at birth, whereas GA at birth significantly impacted survival only after three months of life. Discussion The high morbidity and mortality in preterm and LBW neonates with CHD reflect their complexity and consequent limited treatment feasibility.